Response surface models for the Elliott, Rothenberg, and stock unit-root test (2017)
In this article, we present response surface coefficients for a large range of quantiles of the Elliott, Rothenberg, and Stock (1996, Econometrica 64: 813- 836) unit-root tests, for different combinations of number of observations, T, and lag order in the test regressions, p, where the latter can either be specified by the user or be endogenously determined. The critical values depend on the method used to select the number of lags. We present the command ersur and illustrate its use with an empirical example that tests the validity of the expectations hypothesis of the term structure of interest rates. © 2017 StataCorp LLC.